Split-face comparison between single-band and dual-band pulsed light technology for treatment of photodamage - Varughese, Neal; Keller, Lauren; Goldberg, David J. (Journal of cosmetic and laser therapy, 2016)
Intense pulsed light (IPL) has a well-recognized role in the treatment of photodamaged skin. To assess the safety and efficacy of a novel single-band IPL handpiece versus dual-band IPL handpiece in the treatment of photodamage. This was a prospective, single-center split-face study with 20 enrolled participants. Three treatments, 21 days apart, were administered to the subjects and follow-up was performed for 20 weeks. The left side of the face was treated with the single-band handpiece. The right side of the face was treated with the dual-band handpiece. Blinded investigators assessed the subjects' skin texture, pigmented components of photodamage, and presence of telangiectasia both before and after treatment, utilizing a five-point scale. Pigmented components of photodamage, skin texture, and presence of telangiectasias on the left and right side of the face were improved at the end of treatment. At 20-week follow-up, the side treated with single-band handpiece showed improvement in telangiectasia and pigmentation that was statistically superior to the contralateral side treated with the dual-band handpiece. Both devices equally improved textural changes. No adverse effects were noted with either device. Both single-band and dual-band IPL technology are safe and effective in the treatment of photodamaged facial skin. IPL treatment with a single-band handpiece yielded results comparable or superior to dual-band technology.